A Content Management System as an Information Management System in Interdisciplinary Research - Rola, Paweł; Kuchta, Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
Teams of scientific specialists have replaced independent researchers, simultaneously the research team size has increased by 50% over the 19‑year period. Better collaborations between project team members might improve research outcomes or R&D project products. Knowledge needs to be communicated among a research team effectively and shared among all research team members as it is created collaboratively. Collaboration can be successfully supported by providing a knowledge sharing environment and communication facilities. The purpose of this paper is to evaluate the feasibility and discuss novel communication among scientists using a content management system (CMS) which operates based on the Software‑as‑a‑Service (SaaS) cloud‑computing model. This study presents the use of CMS for the collaboration of a research team carrying out a research project funded by the Polish National Science Centre.